Total Quality Management for High Quality Education Strategy at Pondok Modern Darussalam Gontor Ponorogo - Mardiyah, Mardiyah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Quality education is of great concern to many people around the world. In the highly competitive education sector, the success of Islamic boarding schools depends on the quality of education. Total Quality Management (TQM) is a reference for managing quality-based educational institutions. Pondok Modern Darussalam Gontor Ponorogo is one of the Islamic boarding school educational institutions that now exists and has produced active graduates. This cannot be separated from good and quality education management. This study aims to analyze and reveal a TQM-based quality strategy at Pondok Modern Darussalam Gontor. Based on the study, it was found that the implementation of Total Quality Management (TQM) in Islamic boarding schools is carried out by promoting